Evaluation of a Pneumatic Guy-Line Deicing Boot - Govoni, John W.; Franklin, Charles H. (1992)
During the two winter field seasons of 1986-88, a 3-m-long pneumatic cable deicing boot was tested and evaluated by CRREL at the summit of Mt. Washington, New Hampshire. Favorable results from this pilot study led to the development of a longer (14-m) pneumatic boot. This longer boot, which was used to entirely encase one of the guy lines supporting a 9-m-high tower, was evaluated at the summit of Mt. Washington during the 1987-88 icing season. The performance of both pneumatic cable deicing boots during a variety of icing conditions indicates that this simple, cost-effective method of ice prevention on guy wires may be suitable for practical application.